The Role of the Islamic Religious Education Teacher Working Group in Increasing Islamic Religious Education Teachers’ Competence - Marjuah, Hilmiyah; Kamaruddin, Kamaruddin; Sidik, Sidik; Yusra, Yusra (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2023)
This study aimed to: Know the professional competence of Islamic Religious Education teachers in elementary schools in West Palu District and the role of the Islamic Religious Education Teacher Working Group in improving the professional competence of Islamic Religious Education teachers in elementary schools in West Palu District. This type of research is qualitative descriptive research. Data collection methods used are observation, interviews, documentation, data processing techniques, and data analysis through data reduction, data presentation, and drawing conclusions. The results of this study indicate the professional competence of Islamic Religious Education teachers in elementary schools in West Palu District based on indicators of teacher professional competence. The professional competence of Islamic Religious Education teachers still needs to be improved to make it more optimal. This fact can be seen from the Islamic Religious Education teachers in West Palu District elementary school who can plan lessons, can master the material and develop the material, are able to develop professionalism, and are able to evaluate learning. However, Islamic Religious Education teachers in elementary schools in West Palu District have yet to make maximum use of technology. The role of the teacher working group in increasing the professional competence of Islamic Religious Education teachers in West Palu elementary school can be seen in the intensity of the activities carried out, such as activities to broaden insight and knowledge, realize effective learning, and develop the quality of professionalism of Islamic religious education teachers.